Biliary aspergillosis: Unusual presentation with elevated CA19.9 - Krsteska, Blagica; Ilievski, Boro; Kostadinova Kunovska, Slavica; Jovanovikj, Rubens (Japanese Society of Gastroenterology, 2022)
Aspergillosis is a disease caused by a common mould Aspergillus with a wide variety of clinical syndromes. Invasive aspergillosis is the most severe form and usually occurs in immunocompromised patients. Hepatobiliary aspergillosis is uncommin condition encountered in immunocompetent patients. We report a case of aspergillosis in Ampulla of Vater with suspected malignancy due to elevated tumor marker CA19.9, jaundice and high values of liver enzymes. Diagnosis was confirmed by pathohistology and histochemical stain Grocott methenamine silver (GMS)
Keywords: aspergillosis; aspergillus; cholangitis; pancreatic carcinoma; ampulla of vater